2014
DOI: 10.1080/11263504.2014.969353
|View full text |Cite
|
Sign up to set email alerts
|

Seed morphology and its systematic implications for genusOxytropisDC. (Fabaceae)

Abstract: In the present study, seeds of 13 Oxytropis DC. species (including two latest synonyms) classified in subg. Oxytropis (sect. Dolichocarpon, sect. Chrysantha and sect.Eumorpha), subg. Euoxytropis (sect. Orobia), and subg. Phacoxytropis (sect.Protoxytropis, sect. Janthina and sect. Mesogaea) from Turkey were examined using Light and Scanning Electron Microscopy to evaluate the taxonomic relevance of macroand micro-morphological seed characters. As a result of the study, species-specific characters have been dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 20 publications
(24 reference statements)
1
13
0
1
Order By: Relevance
“…Among the notable contributions dealing with the seed coat surface are those of Ponomarenko et al (1990) on species of the genus Cassia, Chernoff et al (1992) on species of Vicieae, Abou-El-Enain and Loutfy (1999) on the genus Sesbania Scop., Zareh (2005) on six species of Hippocrepis L., Abou-El-Enain et al (2007) on the genus Lathyrus, and Zorić et al (2010) on 38 species of the genus Trifolium L. Recently Mirzaei et al (2015) and Erkul et al (2015) published works on the genera Colutea and Oxytropis, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Among the notable contributions dealing with the seed coat surface are those of Ponomarenko et al (1990) on species of the genus Cassia, Chernoff et al (1992) on species of Vicieae, Abou-El-Enain and Loutfy (1999) on the genus Sesbania Scop., Zareh (2005) on six species of Hippocrepis L., Abou-El-Enain et al (2007) on the genus Lathyrus, and Zorić et al (2010) on 38 species of the genus Trifolium L. Recently Mirzaei et al (2015) and Erkul et al (2015) published works on the genera Colutea and Oxytropis, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Los caracteres micromorfológicos y anatómicos de las semillas han sido utilizados como herramientas importantes en estudios taxonómicos de las Fabaceae (Turki et al, 2013;Noori et al, 2014;Mirzaei, et al, 2015), particularmente al examinar su forma, tamaño, color, anatomía, topografía o relieve de la testa, entre otras. En el presente trabajo, el microscopio electrónico de barrido permitió observar que la testa de la semilla de P. laevigata tiene superficie rugoso-punteada, que es característica en otras especies, como P. farcta y P. juliflora (George et al, 2016), y otros géneros de Fabaceae como Indigofera L. (Murthy y Sanjappa, 2002), Colutea L. (Mirzaei et al, 2015), Oxytropis D.C. (Erkul et al, 2014) y Crotalaria L. (Subramaniam et al, 2015). Por ello, es necesario realizar estudios que incluyan análisis de las semillas de otros Prosopis, con la finalidad de identificar su posible significado o importancia taxonómica, para establecer similitudes y diferencias entre distintos taxones (Leython y Jáuregui, 2008).…”
Section: Semillasunclassified
“…Souza and Marcos‐Filho (2001)gave a comprehensive view of the modulatory role played by mature seed coat in Fabaceae and reported that seed cot structures differ among species and varieties. Erkul, Celep, and Aytaç (2014) examined seeds of 13 Oxytropis DC. species from Turkey using Light and SEM to evaluate the taxonomic relevance of macromorphological and micromorphological seed characters.…”
Section: Introductionmentioning
confidence: 99%